Validation of a metadata application profile domain model - Malta, Mariana Curado (2018)
The development of Metadata Application Profiles is done in several phases. According to the Me4MAP method, one of these phases is the creation of the domain model. This paper reports the validation process of a domain model developed under the project POSTDATA - Poetry Standardization and Linked Open Data. The development of the domain model ran with two steps of construction and two of validation. The validation steps drew on the participation of specialists in European poetry and the use of real resources. On the first validation we used tables with information about resources related properties and for which the experts had to fill certain fields like, for examples, the values. The second validation used a XML framework to control the input of values in the model. The validation process allowed us to find and fix flaws in the domain model that would otherwise have been passed to the Description Set Profile and possibly would only be found after implementing the application profile in a real case.